Integrin Activation Through the Hematopoietic Adapter Molecule ADAP Regulates Dendritic Development of Hippocampal Neurons - Thiere, Marlen; Kliche, Stefanie; Müller, Bettina; Teuber, Jan; Nold, Isabell; Stork, Oliver (Frontiers in Molecular Neuroscience, 2016)
Integrin-mediated cell adhesion and signaling is of critical importance for neuronal differentiation. Recent evidence suggests that an “inside-out” activation of β1-integrin, similar to that observed in hematopoietic cells, contributes to the growth and branching of dendrites. In this study, we investigated the role of the hematopoietic adaptor protein adhesion and degranulation promoting adapter protein (ADAP) in these processes. We demonstrate the expression of ADAP in the developing and adult nervous hippocampus, and in outgrowing dendrites of primary hippocampal neurons. We further show that ADAP occurs in a complex with another adaptor protein signal-transducing kinase-associated phosphoprotein-homolog (SKAP-HOM), with the Rap1 effector protein RAPL and the Hippo kinase macrophage-stimulating 1 (MST1), resembling an ADAP/SKAP module that has been previously described in T-cells and is critically involved in “inside-out” activation of integrins. Knock down of ADAP resulted in reduced expression of activated β1-integrin on dendrites. It furthermore reduced the differentiation of developing neurons, as indicated by reduced dendrite growth and decreased expression of the dendritic marker microtubule-associated protein 2 (MAP2). Our data suggest that an ADAP-dependent integrin-activation similar to that described in hematopoietic cells contributes to the differentiation of neuronal cells.